Male Breast Cancer Presenting as Nipple Discharge. (5th December 2011) - Farooq, A.; Horgan, K.
Abstract : Male breast cancer (MBC) is a rare disease and constitutes less than 1% of all breast carcinoma cases. Although MBC most often presents with a palpable mass, failure to recognise the significance of other symptoms may lead to a delay in diagnosis. Nipple discharge (ND) is a rare symptom in men, but it may herald an underlying malignancy. We present two cases of (MBC) presenting with ND and emphasise the importance of this clinical sign in suspecting underlying malignancy and an opportunity for early diagnosis. We also discuss the clinical significance of ND in men in relation to current literature.